Hydrophobic functional liquids based on trioctylphosphine oxide (TOPO) and carboxylic acids. Issue 42 (27th October 2020) - Byrne, Emily L.; O'Donnell, Ruairi; Gilmore, Mark; Artioli, Nancy; Holbrey, John D.; Swadźba-Kwaśny, Małgorzata
Abstract : Hydrophobic eutectic liquids with high TOPO content are promising extractants of valuable solutes from aqueous streams. Abstract : Trioctylphosphine oxide (TOPO) is a hydrophobic extracting agent used in a number of commercially important separations of valuable solutes from aqueous streams (with examples ranging from lanthanides, through gallium, to carboxylic acids). TOPO is traditionally used as a solute in kerosene, its extraction efficiency limited by its solubility in the organic diluents. In this work, eighteen hydrogen bond donors (HBDs) were screened for their capacity to liquefy TOPO, employing strategies used to design deep eutectic solvents (DES). The selected HBDs were all useful in separations and were designed to formulate solvent-free, hydrophobic, bi-functional liquid extracting agents. Some TOPO:HBD mixtures yielded hydrophobic liquids that offer potential to be extremely efficient extractants, incorporating high intrinsic concentrations of TOPO. Following this initial screening, two systems: TOPO:malonic acid and TOPO:levulinic acid, were selected for detailed physico-chemical characterisation across their complete compositional ranges. Phase diagrams, thermal stabilities and the mechanism of thermal decomposition are reported, along with densities and insights from 31 P NMR spectroscopic studies. The work was concluded with a proof-of-concept demonstration of the use of the TOPO:malonic acid (2 : 1 mol ratio) mixture for the extraction of gallium from acidic chloride feedstock (simulated pre-digestate of zinc leach residue). The loading capacity of the TOPO:malonic acid extractant was three orders of magnitude greater than that of the literature benchmark, encouraging further application-oriented studies.